Analisis Kausalitas Pertumbuhan Ekonomi terhadap Indeks Pembangunan Manusia - Muslikhati, Muslikhati (Falah: Jurnal Ekonomi Syariah, 2018)
Human development is one of the indicators of the success of economic growth. The good quality of human resources goes hand in hand with economic growth, this is because resources as part of the factor of production are the most valuable assets in the economic activities of a country. This study aims to determine and analyze the causality of economic growth towards the quality of human resources. The method used in this study was using the Granger Causality method. Granger Causality Approach is used to measure the strength of the relationship between two or more variables, or it can also be used as a tool to see the direction of the relationship between independent variables and the dependent variable. The variable Human Development Index (HDI) as the dependent variable and per capita income variable as the independent variable. From this study it was concluded that the granger causality test on the proposed research model states that there is no causality relationship between two independent variables and the dependent variable, but significantly the Indonesian economic growth variable has a one-way relationship with the human development index (HDI).Human development is one of the indicators of the success of economic growth. The good quality of human resources goes hand in hand with economic growth, this is because resources as part of the factor of production are the most valuable assets in the economic activities of a country. This study aims to determine and analyze the causality of economic growth towards the quality of human resources. The method used in this study was using the Granger Causality method. Granger Causality Approach is used to measure the strength of the relationship between two or more variables, or it can also be used as a tool to see the direction of the relationship between independent variables and the dependent variable. The variable Human Development Index (HDI) as the dependent variable and per capita income variable as the independent variable. From this study it was concluded that the granger causality test on the proposed research model states that there is no causality relationship between two independent variables and the dependent variable, but significantly the Indonesian economic growth variable has a one-way relationship with the human development index (HDI).